AN ANALYSIS OF INTERNET MARKETING IN INDIA: PROSPECTS AND DIFFICULTIES (International Journal of Food and Nutritional Sciences, 2022)
This study examines the state of e-advertising in India, noting its advantages, drawbacks, and outcomes from the growing use of smart phones.The benefits of e-advertising are highlighted in the article, such as its low value, wide attainment, 24x7 accessibility, and enhanced internet site visitors. It then explores the main obstacles that e-advertising methods ought to conquer, consisting of the need to integrate them with traditional advertising projects, privacy and security problems, and the possibility of impersonal customer support. The study also focuses on the task of constructing brand cognizance in a digital space in which customers have the potential to reject classified ads.The article examines secondary data on web and smartphone usage, e-commerce industry improvement, outstanding social media platforms, e-advertising and marketing expenditure, and the impact of e-advertising on positive industries that allow us to realise the prevailing situation of e-advertising in India. The outcomes of these studies indicate that there is a rising emphasis on attaining smartphone users through e-advertising campaigns, on the grounds that there is a vast positive correlation between e-advertising expenditure and the wide variety of smart phone users in a given area. The relevance of e-marketing for Indian firms is emphasised in the paper's conclusion, along with the desire to come up with revolutionary answers to cope with the problems this digital marketing approach presents.